Comparison of Therapeutic Effects of Different Rehabilitation Methods on Patients Undergoing Total Knee Arthroplasty: A Network Meta‐Analysis of Randomized Controlled Trials - Zhaokai Jin; Yi Tang; Hua Huang; Lei Chen; Zhongyi Zhang; Tianyou Ma; Zhengming Wang; Hai Su; Haojing Zhou; Shuaijie Lv; Peijian Tong (Orthopaedic Surgery)
ABSTRACT Objective The rehabilitation methods after total knee arthroplasty (TKA) can affect the recovery of complications and joint function, and the selection and comparison of rehabilitation methods after TKA still need further research. Methods A comprehensive search of five databases and two clinical trial registration platforms was conducted from inception through March 31, 2024, and conducted to identify eligible randomized controlled trials (RCTs). We extracted the required data according to the Cochrane Handbook for Systematic Reviews of Interventions. Finally, 32 trials involving 2292 patients were included, the mean age of the enrolled patients was ~69.10 years, the sex ratio of males was (31.6%), and the longest follow‐up time was 2 years. And we have summarized nine rehabilitation intervention measures: conventional physical therapy (CPT), cryotherapy, thermal therapy (TT), acupuncture, hydrotherapy, neuromuscular training (NT), electrotherapy, continuous passive motion (CPM), continuous active motion (CAM). And use the range of motion (ROM), visual analog scale (VAS), Western Ontario and McMaster Universities osteoarthritis index (WOMAC) as the outcome measure to evaluate the effectiveness of various interventions. A Bayesian network meta‐analysis (NMA) was carried out for calculating standardized mean difference (SMD) and the surface under cumulative ranking curve (SUCRA) of improvement of knee joint function after TKA by different rehabilitation methods. Result After treatment, the ROM results showed that cryotherapy, electrotherapy, and NT had better therapeutic effects. Among them, cryotherapy (WMD = 10.3, 95% CI 1.63–18.2) had a significant therapeutic effect. In terms of VAS, NT and TT showed good therapeutic effects. Among them, NT had a more significant therapeutic effect, while CAM had less effect. After treatment, in terms of WOMAC, TT, hydrotherapy, cryotherapy, and NT had better therapeutic effects. TT had the best therapeutic effect, while Hydrotherapy and Cryotherapy also had certain advantages. Conclusion NT, TT, cryotherapy, hydrotherapy, and electrotherapy rehabilitation therapies have good therapeutic effects for TKA patients compared with other interventions. Among them, NT may be the best postoperative rehabilitation therapy.